Distribution of inorganic arsenic species in mine tailings of abandoned mines from Korea - Kim, MJ; Ahn, KH; Jung, YJ (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
The main objective of the present study is to determine arsenic species in mine tailings by applying an ion exchange method. Three abandoned mines, Jingok, Cheonbo and Sino mines in Korea, which had produced mainly gold, were selected for the collection and analysis of the tailings. It was found that the arsenic speciation using an ion exchange method was effective to separate As(III) and As(V) in leachate of mine tailings. The concentration of As(V) was found to be 63-99% in the leachate, indicating that As(V) would be the major arsenic species in the mine tailings and the tailings were under oxic conditions. The total concentrations of arsenic and metal elements in the mine tailings were up to 62 3 50 mg/kg As, 40 wt.% Fe, 21400 mg/kg Mn, and 7850 mg/kg Al. Sulfate was the dominant anion throughout the leachate, reaching a maximum dissolved concentration of 734 mg/l. The results of XRD and SEM in the mine tailings showed that main arsenic-containing minerals were pyrite (FeS2) and arsenopyrite (FeAsS) which would be the source of arsenic contamination in the study area. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: CONTAMINATED SOIL; SEDIMENT SAMPLES; SPECIATION; GROUNDWATER